Дослідження методів стабілізації відео та будови гіростабілізованих підвісів відеокамер для безпілотних літальних пристроїв - Майданик, О. О.; Мелешко, Є. В.; Мацуй, А. М.; Шимко, С. В.; Maidanyk, О.; Meleshko, Ye.; Matsui, А.; Shymko, S. (ЦНТУ, 2022)
Метою даної роботи було дослідження будови гіростабілізованих підвісів відеокамер для дронів, що застосовуються для механічної стабілізації відео при відеоспостереженні або візуальній навігації. Від якості стабілізації відео залежить і якість отриманого зображення з дрону, а отже і кількість одержаної корисної інформації. Існує дві основні групи методів стабілізації відео: оптико-механічна та цифрова стабілізація. Для максимального покращення якості зображення з відеокамери безпілотного літального апарату (БПЛА) та зведення до мінімуму наслідків дрижання камери, необхідно в першу чергу виконувати механіко-оптичну стабілізацію відео, а потім за необхідності доповнювати її цифровою стабілізацією. Тільки цифрова стабілізація без механіко-оптичної виконується лише з метою здешевлення дрону. Оптико-механічна стабілізація зазвичай базується на показах гіроскопу. У даній роботі було проведено порівняльне дослідження наступних методів механічної стабілізації відео з БПЛА: на основі 3-х та 2-х осьових гіростабілізованих підвісів з одним мікроконтролером та на основі гіростабілізованих підвісів з енкодерами і декількома мікроконтролерами. The goal of this paper was to research the construction of gyro-stabilized video camera suspensions for drones used for mechanical video stabilization during video monitoring or aerial exploration. The quality of the image received from the drone depends on the quality of the video stabilization, and therefore the amount of useful information received. There are two main groups of video stabilization methods: optical-mechanical and digital stabilization. In order to maximize the quality of the image from the video camera of the unmanned aerial vehicle and to minimize the effects of camera shake, it is necessary to first perform mechanical-optical video stabilization, and then, if necessary, supplement it with digital stabilization. Only digital stabilization without mechano-optical is performed only for the purpose of making the drone cheaper. Optical-mechanical stabilization is usually based on gyroscope readings. In this work, comparative research of the following methods of mechanical stabilization of video from drones was conducted: based on 3-axis and 2-axis gyro-stabilized suspensions with one microcontroller and based on gyro-stabilized suspensions with encoders and several microcontrollers. Mechanical stabilization, in addition to leveling the position of the camera when maneuvering the drone, allows you to turn the camera to a convenient viewing angle for the operator of a drone. 2-axis and 3-axis suspensions with one microcontroller have become the most popular because of their convenience and practicality. 1-axis suspensions or rigidly fixed cameras are used less often. Rigidly fixed cameras are used as course guides for orientation in space by the operator of a drone. That is, such a camera makes it possible to understand the deviation of the drone from the horizon and to adjust the command to the operator for correct flight. Rigid cameras are also used on drones for drone racing competitions. A modular system based on magnetic encoders and several microcontrollers is just beginning to develop, but such a system has a number of advantages, although it is more complicated and expensive. The system provides high accuracy and reliability of stabilization. Each module of the system performs its task. In this way, the resources of microcontrollers are distributed. But its main feature is maintaining the position of the axis rotors relative to the encoder readings. This makes it possible to react very precisely to dynamic actions on the system during active maneuvering of the drone.
Research of Video Stabilization Methods and of the Construction of Video Camera Gyro-stabilized Suspensions for Drones
Keywords: дрон; безпілотний літальний апарат; гіростабілізовані підвіси відеокамер; цифрова стабілізація відео; механічна стабілізація відео; відеоспостереження; drone; unmanned aerial vehicle; gyro-stabilized video camera suspensions; digital video stabilization; mechanical video stabilization; video monitoring; aerial exploration